On Certain Summation Formulae Involving Gauss Theorem (Global Journal of Science Frontier Research, 2013)
The main object of present paper is to obtain some summation formuale involving Contiguous relation, Recurrence relation, Gauss second summation theorem and Legendre duplication formula.
Keywords: contiguous relation; recurrence relation; gauss second summation theorem; legendre duplication formula